Effect of ethanol addition on the laminar burning velocities of gasoline surrogates. (1st November 2022) - Shankar, V.; Fang, X.H.; Hinton, N.; Davy, M.; Leach, F.C.P.
Abstract: Laminar burning velocities (LBV) and Markstein lengths of spherical flames of n-heptane (H), iso-octane (O), and ethanol (E) and their binary and ternary mixtures (in equal volume fractions) at elevated pressures and temperatures are experimentally investigated. Measurements are performed in a constant volume combustion vessel using two distinct techniques: flame front imaging and pressure rise rate. For pure components, ethanol shows a higher LBV compared to n-heptane and iso-octane at same conditions. A pressure dependence on LBV of each pure component is observed where ethanol is found to have the strongest pressure dependence. This is also indicated by the higher negative coefficients in three-body termination reactions through a sensitivity analysis. For binary mixtures, the EH mixture was found to have the highest LBVs compared to other blends. The pressure dependence on LBV of ethanol is also present in binary mixtures where at a higher pressures the EO blend is found to have a lower LBV compared to the OH blend due to competing reactions against the H radical pool. Non-linear behaviour of the EH mixture's LBV was observed and verified through the chemical kinetics suggesting the widely used mixing rules for blends might need additional improvements, especially at higher temperatures. An equal volume EHO ternary mixture shows the LBV to be similar to the OH mixture at 380 K. At 450 K, the LBVs differ by 7% at atmospheric pressure, but due to ethanol's pressure dependence, this difference decreases to zero as the pressure increases to 4 bar. Highlights: Burning velocities of EPRF components shown at elevated temperatures and pressures. Burning velocities of binary and ternary mixtures presented at same conditions. Flame front imaging and pressure rise rate methods show consistent results. Ethanol displays a strong pressure dependence at higher temperatures. Mixing rules fail for ethanol and n-heptane binary blends.